Chromatic pupillometry for the characterization of the pupillary light reflex in Octodon degus. (January 2020) - Palanca-Castan, Nicolas; Harcha, Paloma A.; Neira, David; Palacios, Adrian G.
Abstract: The common degu ( Octodon degus ) is an emerging model in biomedical science research due to its longevity and propensity to develop human-like conditions. However, there is a lack of standardized techniques for this non-traditional laboratory animal. In an effort to characterize the model, we developed a chromatic pupillometry setup and analysis protocol to characterize the pupillary light reflex (PLR) in our animals. The PLR is a biomarker to detect early signs for central nervous system deterioration. Chromatic pupillometry is a non-invasive and anesthesia-free method that can evaluate different aspects of the PLR, including the response of intrinsically photosensitive retinal ganglion cells (ipRGCs), the disfunction of which has been linked to various disorders. We studied the PLR of 12 degus between 6 and 48 months of age to characterize responses to LEDs of 390, 450, 500, 525 and 605 nm, and used 5 with overall better responses to establish a benchmark for healthy PLR (PLR+) and deteriorated PLR (PLR-). Degu pupils contracted up to 65% of their horizontal resting size before reaching saturation. The highest sensitivity was found at 500 nm, with similar sensitivities at lower tested intensities for 390 nm, coinciding with the medium wavelength and short wavelength cones of the degu. We also tested the post-illumination pupillary response (PIPR), which is driven exclusively by ipRGCs. PIPR was largest in response to 450 nm light, with the pupil preserving 48% of its maximum constriction 9 s after the stimulus, in contrast with 24% preserved in response to 525 nm, response driven mainly by cones. PLR- animals showed maximum constriction between 40% and 50% smaller than PLR+, and their PIPR almost disappeared, pointing to a disfunction of the iPRGCs rather than the retinal photoreceptors. Our method thus allows us to non-invasively estimate the condition of experimental animals before attempting other procedures. Highlights: We developed a specific method for chromatic pupillometry in degu. This is the first characterization of the pupillary light reflex in this animal. There were differences between healthy and deteriorated animals. This method could help detect neurodegeneration within an experimental colony.